Analysis of Kurikulum Merdeka development and its application in classroom accounting learning - Diah Amalia; Sofa Nabila; Myisha Azlia Nafhatus Sofa; Intan Desyanti (Himpunan Pengembang Kurikulum Indonesia, 2025)
Kurikulum Merdeka can not only improve the quality of education, but can also build highly competitive human resources to meet the needs of the times. This research article discusses the development of a kurikulum merdeka and its influence on accounting learning in the classroom. This research aims to give freedom to educational institutions, educators, and students in determining the learning process. In this research, the curriculum plays an important role as a learning guide and a tool to develop abilities, shape character, and improve student competencies. The curriculum is designed to prepare students to face global challenges that continue to grow and answer various educational challenges in the digital era and globalization. This research uses a qualitative descriptive method to describe the situation factually. Data was collected by conducting interviews, documentation, and literature studies. The results of this study indicate that the success in developing the kurikulum merdeka is greatly influenced by collaboration between the principal, deputy principal for curriculum, program leader, teachers, and library managers. Implementing the kurikulum merdeka in schools, which are the objects of research, shows success in curriculum development. Not only has it succeeded in developing a curriculum that meets national education standards, but it is also relevant to the world of work demands. Abstrak Kurikulum Merdeka tidak hanya dapat meningkatkan kualitas pendidikan, tetapi juga dapat membangun sumber daya manusia yang berdaya saing tinggi untuk memenuhi kebutuhan zaman. Penelitian artikel ini membahas tentang pengembangan kurikulum merdeka dan pengaruhnya terhadap pembelajaran akuntansi di kelas. Tujuan dari penelitian ini adalah untuk memberikan kebebasan kepada institusi pendidikan, pendidik, dan peserta didik dalam menentukan proses pembelajaran. Pada penelitian ini kurikulum berperan penting sebagai panduan belajar dan alat untuk mengembangkan kemampuan, membentuk karakter, dan meningkatkan kompetensi peserta didik. Kurikulum dirancang untuk mempersiapkan peserta didik menghadapi tantangan global yang terus berkembang serta menjawab berbagai tantangan pendidikan di era digital dan globalisasi. Metode pada penelitian ini menggunakan metode deskriptif kualitatif untuk menggambarkan keadaan secara faktual. Pengumpulan data yang dilakukan dengan melakukan wawancara, studi dokumentasi, dan studi literatur. Hasil dari penelitian ini menunjukkan bahwa keberhasilan dalam pengembangan Kurikulum Merdeka sangat dipengaruhi oleh kolaborasi antara kepala sekolah, wakil kepala sekolah bidang kurikulum, ketua program, para pendidik, dan pengelola perpustakaan. Implementasi kurikulum merdeka pada sekolah yang menjadi objek penelitian menunjukkan keberhasilan dalam pengembangan kurikulum. Tidak hanya berhasil mengembangkan kurikulum yang memenuhi standar pendidikan nasional, tetapi juga relevan dengan tuntutan dunia kerja. Kata Kunci: Kurikulum Merdeka; pembelajaran akuntansi; pengembangan kurikulum